Uniform Hollow Mesoporous Nickel Cobalt Sulfide Microdumbbells: A Competitive Electrode with Exceptional Gravimetric/Volumetric Pseudocapacitance for High‐Energy‐Density Hybrid Superapacitors. (3rd January 2017) - Hou, Linrui; Bao, Ruiqi; Rehan, Muhammad; Tong, Liuniu; Pang, Gang; Zhang, Xiaogang; Yuan, Changzhou
Abstract : In this contribution, a facile two‐step hydrothermal protocol to prepare hierarchical uniform hollow mesoporous NiCo2 S4 microdumbbells (NCS‐MDs) for advanced supercapacitors is developed. Physicochemical investigations reveal that the as‐obtained NCS‐MDs with mesoporous channels in nanoshells possess high‐content Co(III) and Ni(III) species, large surface area (≈80 m 2 g −1 )/pore volume (≈0.12 m 3 g −1 ), and high tap density (≈0.8 g cm −3 ). When evaluated as an attractive pseudocapacitive electrode, the unique NCS‐MDs with mass loading of 7 mg cm −2 exhibit remarkable gravimetric/volumetric specific capacitances of ≈912 F g −1 (≈729 F cm −3 ) at 3 A g −1, and even ≈767 F g −1 (≈613 F cm −3 ) at high current density of 10 A g −1 . Additionally, capacitive degradations of ≈13% and ≈18% are observed over 5000 continous cycles at current rates of 6 and 10 A g −1, respectively. Furthermore, a high‐energy‐density hybrid device is fabricated by using hollow NCS‐MDs and biomass‐derived activated carbon as positive and negative electrodes, respectively, and delivers striking energy density of ≈35.4 Wh kg −1 at power density of ≈381.2 W kg −1, and excellent electrochemical stability at various rates over 11 000 consecutive cycles. These fascinating features strongly highlight that the as‐resulted hollow mesoporous NCS‐MDs could be highly anticipated as a promising electrode platform for next‐generation hybrid supercapacitors. Abstract : Uniform hollow mesoporous NiCo2 S4 microdumbbells are fabricated and exhibit exceptional gravimetric/volumetric pseudocapacitances for advanced hybrid supercapacitors, thanks to its synergetic contribution from compositional and structural merits.